Pinus gerardiana: A boon for livelihood security in Jammu and Kashmir - Masood, Manzar; Slathia, P. S.; Gupta, S.K.; Peshin, R.; Kumar, Rakesh (Indian Journal of Agroforestry, 2020)
Pinus gerardiana Wall. (Chilgoza) is an edible pine nut of North-Western Himalayas. The species is of great importance in the dry temperate zone due to its pivtol role in the economy of the tribal. The present study was conducted in Paddar block of Kishtwar district in Jammu and Kashmir in 2012-13. Out of 32 villages were randomly selected having the dominance of chilgoza plantations in Paddar block and 10 respondents per village were interviewed through pre-structured schedule. The investigation was carried out to study the socio-economic profile of the study area and the percent contribution of chilgoza nut collection, extraction and marketing to the family income. Data depicted that maximum (64.88 percent) income was obtained from chilgoza nut collection in Affani village than crops and labour wages per household. On average basis of the selected villages chilgoza nut collection contributed 43.56 percent in total household economy of the Padder Valley. Unscientific storage of nuts was the major constraint reported by 86.25 percent of the sampled farmers and 66.25 per cent of the respondents also reported that local unskilled manpower engaged for nut extraction damage the nuts due to lack of proper scientific knowledge there by lowering its quality. Since, chilgoza (Pinus gerardiana) play a vital role in the livelihood of rural people, it is necessary to provide the technical know-how to address to the scientific storage and nut extraction so that net returns increase further thereby improving the socio-economic status of the farmers.